Tantangan dan Strategi Penerapan Lingkungan Bahasa Arab di Pesantren - Muhammad Samin, Saproni; Akzam, Ismail; Pebrian, Rojja; Fikriansyah, Mahmud Harits (UIR Press, 2025)
This study seeks to develop a strategy for the implementation of a conducive Arabic language environment in Islamic boarding schools. This study employs a qualitative research method with a descriptive research design. The target population consists of Islamic boarding schools in Riau that offer an Arabic language teaching program. The research sample comprises 12 Islamic boarding schools selected purposively based on the criteria of having an Arabic language teaching program and having participated in the community service program